Removal of Cyanobacteria and Cyanotoxins by Membrane Processes - Dixon, Mike B.; Ho, Lionel; Antoniou, Maria G. (My University, 2020)
Incorporation of membranes in water and wastewater treatment plants is becoming increasingly popular, especially when high quality end-product is needed. This chapter provides an overview of the efficiencies of low- and high-pressure membranes used for the removal of intracellular (microfiltration and ultrafiltration) and extracellular (nanofiltration and reverse osmosis) cyanotoxins, respectively. The removal of taste and odor compounds with high pressure membranes is also discussed. Details on the application of commercially available membranes are provided in terms of removal of cyanobacterial metabolites and membrane performance (including fouling). Based on the cited literature, it becomes apparent that the rejection percentage of a solute by high-pressure membranes is affected by various properties of the membrane, including its molecular weight cut-off, desalting degree, porosity, morphology, and hydrophobicity as well as the charge and hydrophobicity of the solute and matrix. Finally, the results from an integrated study combining coagulation, activated carbon adsorption, and membrane filtration for the removal of cyanobacteria and cyanotoxins are discussed.
Keywords: cyanotoxins; cyanobacteria; fouling; microfiltration; nanofiltration; reverse osmosis; ultrafiltration; geosmin; methylisoborneol